The Development of Language Skills in the Aspects of Syntax, Semantics, and Pragmatics in Children Aged 5-6 Years - Nurlatifah, Caturiska; Wiliyanto, Dian Atnantomi; Soesyasmoro, R. Asto (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
Children's language abilities are critical and require significant attention. Children with strong language skills can establish effective communication and social interactions within the community. Moreover, their language proficiency can also affect their academic achievements in school. This study aims to explore the profile and factors influencing the language development of children aged 5-6 years at Aisyiyah 5 Semanggi Kindergarten, Surakarta. The research employs a mixed-method approach using a convergent design, which combines different forms of data. Qualitative data collection methods include observation, documentation, and interviews, while quantitative data are gathered through three tests designed to measure syntax, semantics, and pragmatics skills. The study subjects consist of 20 children selected using purposive sampling. The results indicate that the syntax abilities of children aged 5-6 years at Aisyiyah 5 Semanggi Kindergarten are high, while their semantic and pragmatic abilities are very high. However, some respondents exhibit low to moderate abilities. These findings suggest that enhancing children's language skills can be achieved by improving language stimulation through parental caregiving at home and by increasing the role of teachers in providing additional learning media during classroom activities.